Ensuring today and for all times, democracy and respect for human dignity in Argentina - Magnanego, Florencia (2015)
In Raul Alfonsin's speech of 10 December, 1983, there is a constitution of the people as a citizen and the (re) establishment of democracy after the military dictatorship between 1976 and 1983. The construction of the audience is articulated with an ethos of humility: Alfonsin represents himself as "the most humble of Argentines" and as representative of the citizens. We analize how he refer to the situation of enunciation with the metaphor-cliché of the "celebration" in relation to democracy ("the celebration of Argentine democracy" and how in Alfonsin's address, democracy starts in liberal political representation.